(untitled) (American Journal of Human Psychology, 2024)
Lifestyle is gradually shaped by an individual’s daily routine, behavior, and mannerisms. College students develop their lifestyles customary to academic demands and other influences that may construe healthy or unhealthy routines. This study the Health-Promoting Lifestyle profile of college students in the Davao Region using a quantitative analysis approach, which considers gender, department, and year level. The study utilizes the Health-Promoting Lifestyle Profile II (HPLP-II) as its primary tool. A total of 350 students were randomly selected and their responses were subjected to a Shapiro-Wilk test for normality. The results revealed in Table 4 found significant differences between the different demographic groups and their varying significant effects to HPLP. Respectively, in terms of Gender, the significant difference in HPLP was determined by F (2, 22.3) = 10.2, p <0.001 with an effect size, eta- squared (η2) 0.056, indicating a small size effect. Moreover, the significant differences in Department reported an F (3,99.5) = 4.82, p = 0.003 with an effect size, eta-squared (η2) 0.040, indicating a small size effect. Furthermore, the Year Level differences was revealed by an F (5, 135) = 0.952, p <0.001 with an effect size, eta-squared (η2) 0.087 indicating a medium size effect. The data indicates that Year Level is the most influential demographic profile of respondents. Future researchers can explore a qualitative assessment of the dimensions of HPLP to determine the habitual engagements of students in distinct facets of healthy lifestyles. Anent to the study, it may be possible to gain a more comprehensive understanding of the factors that contribute to the promotion of healthy living practices amongst college students.